Economic growth and environmental sustainability: The role of foreign direct investment and technological innovation on carbon emissions in Ghana - Helina Siripi; Ametus Kuuwill; Mark-Daniels Tamakloe (Research in Globalization, 2024)
Debates on foreign direct investment, technological innovation and carbon emission seem unsettling in the literature. We contribute to the literature by investigating the relationships between foreign direct investment, technological innovation, and carbon emissions in Ghana. Using the Autoregressive Distributive Lag (ARDL) method, the analysis reveals that foreign direct investment contributes to reduced emissions in the short run but significantly increases carbon emissions in the long run, aligning with the pollution haven hypothesis. This indicates that Ghana may have a robust environmental regulation that ensures eco-friendly foreign direct investments in the short run, with weak enforcement of regulations resulting in high emissions in the long term. Technological innovation in the Ghanaian context contributes to increased CO2 emissions. However, the interaction effect of foreign direct investments and technological innovation reduces carbon emissions, emphasizing the importance of aligning foreign investments with sustainable technological advancements in Ghana. The study also identifies the Environmental Kuznets Curve (EKC) effect, where emissions rise with economic growth but decelerate at higher GDP levels. The findings underscore the need for stronger environmental regulations and a shift towards sustainable, cleaner energy and technological development to mitigate the environmental impacts of economic growth in Ghana and similar developing countries.
Keywords: 330; Foreign direct investment; Technological innovation; Carbon emissions; Ghana